A history of economic thought in Sweden - Magnusson, Lars, 1952- author. Link Link
1 online resource (218 pages).
Keywords: Situating key texts and writers in their proper historical context, this book presents a history of Swedish economic thinking from early modern times to the present day.Highlighting key elements of Swedish political, economic and social history allows the book to shed new light on important parts of the story including the development of neo-classical economics from the late 19th century - associated with leading names such as Knut Wicksell, Gustav Cassel and Eli Heckscher - and the rise of the so-called Stockholm school in the 1920s and 30s. But the book also goes back further to explore the Swedish economic literature of the 18th century, particularly its more "liberal" version of mercantilism and cameralism, as well as early modern and medieval developments. Throughout, the book emphasizes the unique nature of much of the economic thinking emanating from Sweden. Emulation and adaption of political economic thinking imported from abroad - primarily the UK, France and German speaking countries - is an important part of this story, but this is shown to be an active process which has resulted in great originality in Swedish economic thought.This book will be of interest to readers in the history of economic thought, economic history, the history of ideas and Swedish history.